2023
DOI: 10.1128/aem.01628-22
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Commensal Escherichia coli Aggravates High-Fat-Diet-Induced Obesity and Insulin Resistance in Mice

Abstract: Although identifying specific microbial taxa associated with obesity and type 2 diabetes remains difficult, certain bacteria may play an important role in initiating metabolic inflammation during disease development. Here, we used a mouse model distinguishable by the presence or absence of a commensal Escherichia coli strain in combination with a high-fat diet challenge to investigate the impact of E. coli on host metabolic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…However, the class Clostridia plays a conflicting role because it was found to have a decreased abundance in NAFLD progression induced by a Western diet [ 40 ]. At the family level, the enrichment of Enterobacteriaceae induced by a HFD has been correlated with impaired glucose homeostasis [ 41 ] and was herein associated with OVX-induced NAFLD. The genus Parabacteroides content was reported to be lower in postmenopausal than in premenopausal women [ 42 ], yet we found it to be higher in the OVX group, and other research has reported that Parabacteroides was enriched in early hepatocellular carcinoma (HCC) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the class Clostridia plays a conflicting role because it was found to have a decreased abundance in NAFLD progression induced by a Western diet [ 40 ]. At the family level, the enrichment of Enterobacteriaceae induced by a HFD has been correlated with impaired glucose homeostasis [ 41 ] and was herein associated with OVX-induced NAFLD. The genus Parabacteroides content was reported to be lower in postmenopausal than in premenopausal women [ 42 ], yet we found it to be higher in the OVX group, and other research has reported that Parabacteroides was enriched in early hepatocellular carcinoma (HCC) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…E. coli was found to be predictive of the development of insulin resistance in postmenopausal obese Caucasian females in Sweden ( 149 ). In a HFD-fed mouse model of obesity, E. coli significantly increased body weight and adiposity, and induced impaired glucose tolerance ( 150 ). Therapeutically, in a human randomized trial, paradoxically, the investigators found that metformin treatment significantly increased amplicon sequence of E. coli variants ( 65 ).…”
Section: Bacteria Closely Related To Obesity and Diabetesmentioning
confidence: 99%
“…The increase of the relative abundance in E. coli , was also observed in patients after VGB or RYGB ( 95 , 97 ). However, colonization of E. coli in germ-free mice led to increased inflammation in liver, adipose tissue and intestinal tissue under a HFD regimen ( 150 ). The role of E. coli in obesity and/or type 2 diabetes is debatable as there are contradictory findings; thus, we need to further clarify the mechanism of action of E. coli in obesity and diabetes in future research.…”
Section: Bacteria Closely Related To Obesity and Diabetesmentioning
confidence: 99%
“…At the same time, these changes were observed to reduce microbial diversity and increase the Firmicutes/Bacteroidetes ratio. Further, at the genus level, saturated fats have been shown to relatively increase gram-negative bacterium including Fusobacterium, Tyzzerella, Anaerotruncus, Lachnospiraceae, Eisenbergiella and Escherichia [126,127,129]. In turn, the production of lipopolysaccharides by these gut bacteria promotes a pro-inflammatory state leading to metabolic endotoxemia and chronic inflammation.…”
Section: Saturated Fatsmentioning
confidence: 99%